Periparturient immunosuppression and strategies to improve dairy cow health during the periparturient period. (October 2016) - Aleri, J.W.; Hine, B.C.; Pyman, M.F.; Mansell, P.D.; Wales, W.J.; Mallard, B.; Fisher, A.D.
Abstract: Common health problems observed during peripartum include milk fever, mastitis, fatty liver disease, ketosis, dystocia, retained placenta, metritis, hypomagnesaemia and abomasal displacements. The increased incidence of health problems observed during the periparturient period can be partly attributed to suboptimal immune responses. Factors contributing to decreased periparturient immunity include the act of parturition itself, impaired leukocytic activity, effects of colostrogenesis and lactogenesis, and associated hypocalcemia and negative energy balance. Nutritional and other management strategies represent a relevant short-term strategy aimed at improving the health and welfare of the transitioning cow. Additionally, it is important to consider improving the health of dairy herds through the genetic selection of animals with enhanced robustness by identifying those with superior disease resistance or resilience in the face of infection. As a consequence these animals are better able to cope with the production and environmental stresses. These may provide long-term selection strategies for improving the health and welfare of the transitioning cow particularly when combined with sound management practices, allowing dairy cattle to reach their full genetic potential. Highlights: In this review we propose immune responsiveness as a survival/longevity trait for improving cattle health and welfare at the transition period.